MINI-LAPAROSCOPIC CHOLECYSTECTOMY: EVOLUTION OF A NEW TECHNIQUE (Journal of Science-Innovative Research in Uzbekistan, 2024)
Since the first laparoscopic cholecystectomy (LC) in 1985, there has been much advancement in laparoscopic surgery in terms of reduction in number and size of ports. We report a new technique of performing mini laparoscopiccholecystectomy using only three ports, 5 mm each. The indications of this procedure include GB polyps, GB dyskinesia, microlithiasis, and idiopathic pancreatitis